Breslau Freizeit und Konsum - Kalinke, Heinke M.; Tobias, Weger; Łukasz, Bieniasz (Schriften des Bundesinstituts für Kultur und Geschichte der Deutschen im östlichen Europa, 2023)
For the first time, this volume compiles essays on aspects of the 19th and 20th century history of leisure and consumption in the Silesian metropolis Breslau. How and where did the inhabitants of Breslau spend their leisure time, what athletic activities did they pursue, where did they shop, what cultural offerings did they enjoy? These questions, among others, are the focus of this volume, which uses an interdisciplinary historical approach.